Female reproductive tract-organ axes - Takada, Kazuhide; Melnikov, Vyacheslav G.; Kobayashi, Ryoki; Komine-Aizawa, Shihoko; Tsuji, Noriko M.; Hayakawa, Satoshi (Frontiers in Immunology, 2023)
The female reproductive tract (FRT) and remote/versatile organs in the body share bidirectional communication. In this review, we discuss the framework of the “FRT-organ axes.” Each axis, namely, the vagina-gut axis, uterus-gut axis, ovary-gut axis, vagina-bladder axis, vagina-oral axis, uterus-oral axis, vagina-brain axis, uterus-brain axis, and vagina-joint axis, is comprehensively discussed separately. Each axis could be involved in the pathogenesis of not only gynecological diseases but also diseases occurring apart from the FRT. Although the microbiota is clearly a key player in the FRT-organ axes, more quantitative insight into the homeostasis of the microbiota could be provided by host function measurements rather than current microbe-centric approaches. Therefore, investigation of the FRT-organ axes would provide us with a multicentric approach, including immune, neural, endocrine, and metabolic aspects, for understanding the homeostatic mechanism of women’s bodies. The framework of the FRT-organ axes could also provide insights into finding new therapeutic approaches to maintain women’s health.